Considering Standards-based Grading: Challenges for Secondary School Leaders (Journal of School Administration Research and Development, 2019)
Rather than awarding points for a combination of worksheet completion, quiz performance, in-class participation, and essay writing, standards-based grading separates academics from non-academic factors and communicates students' progress towards mastery of course or grade-level standards. Some secondary schools are moving towards standards-based grading (SBG) in an attempt to produce more consistent grading practices, however the empirical evidence resulting from this change is mixed. The purpose of this article is to describe principles of standards-based grading, empirical support of SBG, and several common challenges secondary school leaders may face when considering this philosophical shift. Future research recommendations include exploring the perspectives of college students who graduate from high schools using SBG to understand the longer-term successes and shortcomings of the grading system.